2009
DOI: 10.1002/jbm.a.32387
|View full text |Cite
|
Sign up to set email alerts
|

Design of a multiphase osteochondral scaffold III: Fabrication of layered scaffolds with continuous interfaces

Abstract: There is a need to improve current treatments for articular cartilage injuries. This article is the third in a series describing the design and development of an osteochondral scaffold based on collagen-glycosaminoglycan and calcium phosphate technologies for regenerative repair of articular cartilage defects. The previous articles in this series described methods for producing porous, three-dimensional mineralized collagen-GAG (CGCaP) scaffolds whose composition can be reproducibly varied to mimic the composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
160
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(162 citation statements)
references
References 85 publications
(149 reference statements)
2
160
0
Order By: Relevance
“…Due to the complex zonal organisation of osteochondral tissue, development of a single implantable biomaterial with a gradient structure is of great interest in the field of osteochondral tissue engineering [36,37]. This study built on the existing collagenbased scaffold expertise within our research group to develop a novel multi-layered material for osteochondral repair.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the complex zonal organisation of osteochondral tissue, development of a single implantable biomaterial with a gradient structure is of great interest in the field of osteochondral tissue engineering [36,37]. This study built on the existing collagenbased scaffold expertise within our research group to develop a novel multi-layered material for osteochondral repair.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported on the development of tissue engineered osteochondral grafts [3][4][5][6]17,21,[23][24][25]27,33,34,39,57,59,[70][71][72][73][74][75]78,79,83 that have demonstrated significant potential. Most of these osteochondral grafts use a stratified scaffold design that facilitates the development of both cartilaginous and bony regions.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] CG scaffolds have also been adapted for a variety of orthopedic applications covering osteochondral, bone, and tendon tissue engineering. [18][19][20][21] We have recently demonstrated a directional freeze-drying method to create geometrically anisotropic CG scaffolds with aligned tracks of ellipsoidal pores that mimic elements of native tendon anisotropy. 21 While we showed that the platelet-derived growth factor BB (PDGF-BB) and the insulin-like growth factor 1 (IGF-1) promoted increased tenocyte proliferation and migration within these anisotropic scaffolds, 21 a major concern remains the trade-off between increased proliferation and retention of the tenocyte-associated phenotype.…”
Section: Introductionmentioning
confidence: 99%